BUDAYA PATRIARKI DALAM PERS INDONESIA MASA ORDE BARU = PATRIARCHY CULTURE IN INDONESIAN PRESS OF NEW ORDER ERA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT It could not be denied if the condition of women in patriarchal society, like Indonesia, is very bad. Such a condition is created by the social and cultural construction that put the women in subordinated position, while men in dominated one. The unhealthy relationship makes women merely as the object of men in society. Press is one of the means that can be used to look at the bad condition of women in society. Women in some news show the gender bias of journalism practices. There are three main elements should be considered in discussing the gender bias of journalism practices: press, culture, and women. These elements are interrelated in representing women as object creatures in some news. Based on the elements mentioned above, the writer could formulate three conditions in gender bias of New Order journalism practices, especially in two national newspapers. First, a press disability to reveal the truth about women and their existences. Second, women representation in New Order press is a gloomy representation. Third, a gender bias of journalism practices are caused by several reasons in patriarchal society. The three conditions, that do not make any advantages to women, have a correlation with the reality in society. Such a reality signals that women have been conditioned by the society order with unpleasant position. Through values and meanings in society, the construction of unbalanced relation of women and men have been communicated by using symbols and myths. Even state and press have adopted the construction. In the communication context, it permeates in press institution such as a newspaper. As a mirror of reality, a newspaper also has an ability to reflect it. The gloomy reality of women in a newspaper is an undeniable fact. By realizing the gender bias of journalism practices, the construction of women discourse needs a reconscientization, reawareness, that women are women. Keyword: Patriarchy Culture -- Gender Indonesian Press